2015
DOI: 10.1038/cddis.2015.266
|View full text |Cite
|
Sign up to set email alerts
|

RILP suppresses invasion of breast cancer cells by modulating the activity of RalA through interaction with RalGDS

Abstract: RILP (Rab7-interacting lysosomal protein) is a key regulator for late endosomal/lysosomal trafficking, and probably a tumor suppressor in prostate cancer. However, the role of RILP in other cancers and the underlying mechanism for RILP in regulating the invasion of cancer cells remain to be investigated. In this study, we showed that overexpression of RILP in breast cancer cells inhibits the migration and invasion, whereas the depletion of RILP by RNAi-mediated knockdown promotes the migration and invasion. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
(73 reference statements)
1
19
0
Order By: Relevance
“…Cell migration assay was performed using Transwell chambers with 8.0 μm pore membrane as described previously [ 28 ]. Briefly, after infection with LV-SHCBP1, LV-shSHCBP1, or LV-Control for 72 h, cells were harvested and resuspended in serum-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration assay was performed using Transwell chambers with 8.0 μm pore membrane as described previously [ 28 ]. Briefly, after infection with LV-SHCBP1, LV-shSHCBP1, or LV-Control for 72 h, cells were harvested and resuspended in serum-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…It has been recently shown that RILP depletion in MCF7 (breast adenocarcinoma) cells causes a faster closure of the wound in wound-healing assay demonstrating a role of RILP in cell migration. 19 In order to better characterize this role of RILP and to investigate if this is restricted to breast cancer cells we performed a woundhealing assay on NCI H1299 (lung carcinoma) cells transfected with either control RNA or siRNA against RILP. Confluent monolayers of cells were scratched with a pipette tip and migrating cells were imaged at time intervals of 30 min over an 8-h time period.…”
Section: Resultsmentioning
confidence: 99%
“…19 Therefore, the effect of RILP silencing on cell velocity could be mediated by RalGDS. However, RalGDS does not interact with the mutated form of RILP, RILP-C33 that affects adhesion and spreading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of BPA-vs. E2-treated cultures revealed alterations in extracellular matrix organization, glycolytic process, cell migration, and activation of Ral GTPase activity. Recently, RalA activity was shown to promote the invasion of breast cancer cells in vitro (22). All 10 of the biological processes affected by both Pht and PCB were defined by a single protein per process.…”
Section: Functional Classes Of Proteins and Pathways Changed By Exposmentioning
confidence: 99%